Battery

By using LiαMβOγXδ as the first solid electrolyte material in the battery and combining halide or sulfide solid electrolyte material, the discharge capacity and charge and discharge characteristics of the battery are improved, and the problems of low discharge capacity and hydrogen sulfide generation in the existing battery are solved. High output characteristics and thermal stability are achieved.

CN113892206BActive Publication Date: 2024-12-13PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080037194.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-04
Filing Date
2020-03-17
Publication Date
2024-12-13
Estimated Expiration
2040-03-17

AI Technical Summary

Technical Problem

The discharge capacity of the existing batteries is insufficient, and the ion conductivity and thermal stability of the solid electrolyte material need to be improved, and there are problems in the production of hydrogen sulfide.

Method used

LiαMβOγXδ is used as the first solid electrolyte material, and combined with the halide or sulfide solid electrolyte material in the second electrolyte layer to ensure that its reduction potential is lower than the first electrolyte material, and the α, β, γ, and δ values ​​in the chemical formula are adjusted. and molar ratio, improve ion conductivity, and avoid reduction and decomposition through discharge termination voltage control.

Benefits of technology

The high discharge capacity and excellent charging and discharging characteristics of the battery are achieved, and the production of hydrogen sulfide is avoided, and the output characteristics and thermal stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113892206B_ABST
    Figure CN113892206B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a battery with a high discharge capacity. The battery comprises a positive electrode, a first electrolyte layer, a second electrolyte layer and a negative electrode in sequence, wherein the first electrolyte layer contains a first solid electrolyte material, the second electrolyte layer contains a second solid electrolyte material which is a material different from the first solid electrolyte material, and the first solid electrolyte material is represented by the following chemical formula (1): Li α M β O γ X δ Indicates that, here, α, β, γ and δ are all values ​​greater than 0, M is an element selected from at least one of metal elements and semi-metal elements other than Li, X is an element selected from at least one of Cl, Br and I, and the reduction potential of the second solid electrolyte material is lower than the reduction potential of the first solid electrolyte material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a battery. Background Art

[0002] Patent Document 1 discloses an all-solid-state battery using a halide solid electrolyte.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2006-244734 Summary of the invention

[0006] Problems to be solved by the invention

[0007] An object of the present invention is to provide a battery having a high discharge capacity.

[0008] Means for solving problems

[0009] The present invention relates to a battery comprising a positive electrode, a first electrolyte layer, a second electrolyte layer and a negative electrode in this order, wherein the first electrolyte layer contains a first solid electrolyte material, and the second electrolyte layer contains a second solid electrolyte material which is a material different from the first solid electrolyte material, wherein the first solid electrolyte material is represented by the following chemical formula (1):

[0010] Li α M β O γ X δ (1)

[0011] Here, α, β, γ and δ are all values ​​greater than 0, M is an element selected from at least one of metal elements and semi-metal elements other than Li, X is an element selected from at least one of Cl, Br and I, and the reduction potential of the second solid electrolyte material is lower than the reduction potential of the first solid electrolyte material.

[0012] Effects of the Invention

[0013] According to the present invention, the discharge capacity of a battery can be increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A cross-sectional view of a battery 1000 according to the first embodiment is shown.

[0015] Figure 2 It is a graph showing the charge and discharge characteristics of the secondary battery of Example 1.

[0016] Figure 3 It is a graph showing the charge and discharge characteristics of the secondary battery of Example 2.

[0017] Figure 4 It is a graph showing the charge and discharge characteristics of the secondary battery of Example 3.

[0018] Figure 5 It is a graph showing the charge and discharge characteristics of the secondary battery of Example 4.

[0019] Figure 6 It is a graph showing the charge and discharge characteristics of the secondary battery of Comparative Example 1. DETAILED DESCRIPTION

[0020] Below, while referring to the attached Figure 1 Embodiments of the present invention will be described below.

[0021] (First Embodiment)

[0022] Figure 1 It is a cross-sectional view schematically showing the structure of the battery 1000 according to the first embodiment.

[0023] The battery 1000 includes a positive electrode 101 , a first electrolyte layer 102 , a second electrolyte layer 103 , and a negative electrode 104 in this order.

[0024] The first electrolyte layer 102 contains a first solid electrolyte material.

[0025] The second electrolyte layer 103 contains a second solid electrolyte material which is a material different from the first solid electrolyte material. The second solid electrolyte material has a reduction potential lower than that of the first solid electrolyte material.

[0026] The first solid electrolyte material is a material represented by the following chemical formula (1).

[0027] Li α M β O γ X δ (1)

[0028] Here, α, β, γ, and δ are all values ​​greater than 0. M is at least one element selected from metal elements and semi-metal elements other than Li. X is at least one element selected from Cl, Br, and I.

[0029] According to the above configuration, the battery of the first embodiment has a high discharge capacity.

[0030] The first solid electrolyte material has high ion conductivity, so a battery with high output characteristics can be realized. The first solid electrolyte material also has excellent thermal stability. Furthermore, the first solid electrolyte material does not contain sulfur, so no harmful hydrogen sulfide is generated.

[0031] The first solid electrolyte material is an example of an oxyhalide solid electrolyte. Other examples of oxyhalide solid electrolytes are materials formed of Li, O and X (X is at least one element selected from Cl, Br and I), but the first solid electrolyte material containing M has a higher ion conductivity. Therefore, by using the first solid electrolyte material, the battery has high output characteristics.

[0032] In the present invention, the "semi-metallic element" refers to B, Si, Ge, As, Sb and Te.

[0033] In the present invention, "metal elements" refer to (i) all elements contained in Groups 1 to 12 of the periodic table (but excluding hydrogen) and (ii) all elements contained in Groups 13 to 16 (but excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se).

[0034] In order to improve the ion conductivity of the first solid electrolyte material, M may contain at least one element selected from Nb and Ta. The improvement in ion conductivity enables the battery to have a high discharge capacity.

[0035] In order to improve the ionic conductivity of the first solid electrolyte material, the chemical formula (1) may also satisfy

[0036] 0.9≤α≤1.2,

[0037] β=1.0,

[0038] 1.0≤γ≤1.3, and

[0039] 3.6≤δ≤4.0.

[0040] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0041] In order to improve the ion conductivity of the first solid electrolyte material, in the chemical formula (1), the molar ratio of Li to M may be 0.6 to 2.4, and the molar ratio of O to X may be 0.16 to 0.35. The improvement in ion conductivity enables the battery to have a high discharge capacity.

[0042] In order to improve the ion conductivity of the first solid electrolyte material, the first solid electrolyte material may be a material represented by the following chemical formula (A1).

[0043] Li x MeO y X (5+x-2y) (A1)

[0044] Me is at least one element selected from Nb and Ta. X is at least one element selected from Cl, Br and I. Furthermore, 0.1<x<7.0 and 0.4<y<1.9 are satisfied. The battery has a high discharge capacity due to the improvement of the ion conductivity.

[0045] In order to improve the ion conductivity of the first solid electrolyte material, the solid electrolyte material of the first embodiment may be a material represented by the following chemical formula (A2).

[0046] Li 2+b-3a La a OX b (A2)

[0047] Here, 1.0≤a≤2.0 and 1.5≤b≤6.0 are satisfied.

[0048] In order to improve the ion conductivity of the first solid electrolyte material, the solid electrolyte material of the first embodiment may be a material represented by the following chemical formula (A3).

[0049] Li 2+b-3a (Sm 1-x A x ) a OX b (A3)

[0050] Here, A is at least one element selected from the group consisting of Y, La, and Gd. Furthermore, 1.0≤a≤2.17, 1.5≤b≤6.0, and 0≤x≤0.5 are satisfied.

[0051] In order to make the battery of the first embodiment have excellent discharge characteristics, the discharge end voltage of the battery may be 2.9 V or more relative to lithium. In other words, in the control method (e.g., discharge method) of the battery of the first embodiment, the discharge end voltage of the battery may be set to 2.9 V or more.

[0052] During discharge, Li that moves from the negative electrode to the positive electrode is inserted into the positive electrode active material while accompanying the charge transfer reaction. At this time, the solid electrolyte present near the positive electrode active material sometimes undergoes reduction decomposition. Under the action of the current generated by the reduction decomposition, the apparent discharge capacity of the battery can be increased. The presence or absence of reduction decomposition can be determined by the voltage-capacity curve (e.g. Figures 2 to 6 )judge.

[0053] As described above, by setting the discharge end voltage of the battery of the first embodiment to 2.9 V or more with respect to lithium, the battery can be operated without causing reduction decomposition of the first solid electrolyte material and the second solid electrolyte material. That is, the battery has excellent discharge characteristics.

[0054] The voltage that causes the reduction reaction of the solid electrolyte (ie, the lower end voltage of the potential window or the reduction potential) can be measured by the cyclic voltammetry method described in Non-Patent Document 1: "Adv. Energy Mater. 2016, 20, 1501590-1501599.".

[0055] The second solid electrolyte material may also be a halide solid electrolyte (but excluding an oxyhalide solid electrolyte).

[0056] The halide solid electrolyte has high ion conductivity and excellent thermal stability, similar to the first solid electrolyte material. Therefore, by making the first electrolyte layer 102 contain the first solid electrolyte material and the second electrolyte layer contain the halide solid electrolyte (for example, a material represented by the chemical formula (2) described later), a battery with high output characteristics and thermal stability can be achieved.

[0057] In order to make the battery of the first embodiment have excellent discharge capacity, the second solid electrolyte material may also be a halide solid electrolyte represented by the following chemical formula (2).

[0058] Li p M' q X' r (2)

[0059] Here, p, q, and r are all values ​​greater than 0. M' is at least one element selected from metal elements and semi-metal elements other than Li. X' is at least one element selected from Cl, Br, and I.

[0060] In order to improve the ion conductivity of the second solid electrolyte material, M' in the chemical formula (2) may contain Y (=yttrium). The improvement in ion conductivity enables the battery to have a high discharge capacity.

[0061] In order to improve the ionic conductivity of the second solid electrolyte material, the second solid electrolyte material containing Y may also be made of, for example, Li a Me' b Y c A halide solid electrolyte represented by the chemical formula of X'6. Here, a+mb+3c=6 and c>0 are satisfied. Me' is at least one element selected from metal elements and semi-metal elements other than Li and Y. X' is at least one element selected from Cl, Br and I. m represents the valence of Me'.

[0062] In order to improve the ion conductivity of the second solid electrolyte material, Me' may be at least one element selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb.

[0063] In order to improve the ion conductivity of the second solid electrolyte material, the chemical formula (2) may satisfy 2.7≤p≤3, 1≤q≤1.1, and r=6. The improvement in ion conductivity enables the battery to have a high discharge capacity.

[0064] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B1).

[0065] Li 6-3d Y d X6 (B1)

[0066] Here, X is at least one element selected from the group consisting of Cl, Br and I. Furthermore, 0<d<2 is satisfied.

[0067] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0068] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B2).

[0069] Li 3-3δ Y 1+δ Cl6 (B2)

[0070] Here, 0<δ≤0.15 is satisfied.

[0071] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0072] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B3).

[0073] Li 3-3δ Y 1+δ Br6 (B3)

[0074] Here, 0<δ≤0.25 is satisfied.

[0075] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0076] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B4).

[0077] Li 3-3δ+a Y 1+δ-a Me a Cl 6-x-y Br x I y (B4)

[0078] Here, Me is at least one element selected from the group consisting of Mg, Ca, Sr, Ba, and Zn.

[0079] -1<δ<2,

[0080] 0<a<3,

[0081] 0<(3-3δ+a),

[0082] 0<(1+δ-a),

[0083] 0≤x<6,

[0084] 0<y≤6, and

[0085] (x+y)<6.

[0086] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0087] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B5).

[0088] Li 3-3δ Y 1+δ-a Me a Cl 6-x-y Br x I y (B5)

[0089] Here, Me is at least one element selected from Al, Sc, Ga and Bi.

[0090] -1<δ<1,

[0091] 0<a<2、

[0092] 0<(1+δ-a),

[0093] 0≤x<6,

[0094] 0<y≤6, and

[0095] (x+y)<6.

[0096] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0097] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B6).

[0098] Li 3-3δ-a Y 1+δ-a Me a Cl 6-x-y Br x Iy (B6)

[0099] Here, Me is at least one element selected from Zr, Hf and Ti.

[0100] -1<δ<1,

[0101] 0<a<1.5、

[0102] 0<(3-3δ-a),

[0103] 0<(1+δ-a),

[0104] 0≤x<6,

[0105] 0<y≤6, and

[0106] (x+y)<6.

[0107] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0108] In order to improve the ion conductivity of the second solid electrolyte material, the second solid electrolyte material may be a material represented by the following chemical formula (B7).

[0109] Li 3-3δ-2a Y 1+δ-a Me a Cl 6-x-y Br x I y (B7)

[0110] Here, Me is at least one element selected from Ta and Nb.

[0111] -1<δ<1,

[0112] 0<a<1.2、

[0113] 0<(3-3δ-2a),

[0114] 0<(1+δ-a),

[0115] 0≤x<6,

[0116] 0<y≤6, and

[0117] (x+y)<6.

[0118] Due to the improvement in ion conductivity, the battery has a high discharge capacity.

[0119] As the second solid electrolyte material, for example, Li3YX6, Li2MgX4, Li2FeX4, Li(Al, Ga, In)X4, or Li3(Al, Ga, In)X6 may be used. X is at least one element selected from Cl, Br, and I. "(Al, Ga, In)" means "at least one element selected from Al, Ga, and In".

[0120] In order to make the battery of the first embodiment have a high discharge capacity, the second solid electrolyte material may also be a sulfide solid electrolyte.

[0121] Examples of sulfide solid electrolytes used as the second solid electrolyte material include Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 Furthermore, LiX, Li2O, MO, or Li p MO q Here, M is at least one element selected from P, Si, Ge, B, Al, Ga, In, Fe and Zn. p and q are both natural numbers. X is at least one element selected from F, Cl, Br and I.

[0122] In order to make the battery of the first embodiment have a high discharge capacity, the second solid electrolyte material may also contain lithium sulfide and phosphorus sulfide. The second solid electrolyte material may also be Li2S-P2S5.

[0123] In order to suppress short circuits between the positive electrode 101 and the negative electrode 104 and to increase the output of the battery, the total thickness of the first electrolyte layer 102 and the second electrolyte layer 103 may be 1 μm or more and 300 μm or less.

[0124] In order to increase the discharge capacity of the battery, the first electrolyte layer 102 may contain, for example, 70% by mass or more of the first solid electrolyte material, or 90% by mass or more of the first solid electrolyte material relative to the first electrolyte layer 102. The first electrolyte layer 102 may also be formed only of the first solid electrolyte material.

[0125] To increase the discharge capacity of the battery, the second electrolyte layer 103 may contain, for example, 70% or more of the second solid electrolyte material, or 90% or more of the second solid electrolyte material relative to the second electrolyte layer 103. The second electrolyte layer 103 may also be formed only of the second solid electrolyte material.

[0126] The positive electrode 101 contains a positive electrode active material and an electrolyte material.

[0127] The positive electrode active material is a material that can intercalate and deintercalate metal ions (eg, lithium ions).

[0128] Examples of positive electrode active materials are lithium-containing transition metal oxides (e.g., Li(NiCoAl)O2, Li(NiCoMn)O2, or LiCoO2), transition metal fluorides, polyanions, fluorinated polyanion materials, transition metal sulfides, transition metal sulfur oxides, or transition metal nitrogen oxides. In order to reduce manufacturing costs and increase the average discharge voltage of the battery, lithium-containing transition metal oxides may also be used as positive electrode active materials.

[0129] In order to improve the discharge capacity and energy density of the battery of the first embodiment, the positive electrode active material may be nickel-cobalt-lithium manganese oxide. Nickel-cobalt-lithium manganese oxide may be a compound represented by Li(NiCoMn)O2.

[0130] The positive electrode active material may also have a median particle size of 0.1 μm or more and 100 μm or less. When the positive electrode active material has a median particle size of 0.1 μm or more, the positive electrode active material and the electrolyte material can be well dispersed in the positive electrode 101. As a result, the charge and discharge characteristics of the battery are improved. When the positive electrode active material has a median particle size of 100 μm or less, the lithium diffusion rate in the positive electrode active material is increased. As a result, the battery can operate at a high output power.

[0131] The electrolyte material contained in the positive electrode 101 is, for example, a solid electrolyte.

[0132] The electrolyte material included in the positive electrode 101 may be the first solid electrolyte material. That is, the positive electrode 101 may include the first solid electrolyte material.

[0133] The electrolyte material contained in the positive electrode 101 may be a material different from the first solid electrolyte material. Examples of such materials include sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, complex hydride solid electrolytes, halide solid electrolytes, and oxyhalide solid electrolytes (e.g., the first solid electrolyte material).

[0134] The electrolyte material contained in the positive electrode 101 may also be a sulfide solid electrolyte.

[0135] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12. You can also add LiX, Li2O, MO q , or Li p MO q Here, X is at least one element selected from F, Cl, Br and I. M is at least one element selected from P, Si, Ge, B, Al, Ga, In, Fe and Zn. p and q are both natural numbers.

[0136] The electrolyte material contained in the positive electrode 101 may also be an oxide solid electrolyte.

[0137] Examples of oxide solid electrolytes are

[0138] (i) NASICON type solid electrolytes such as LiTi2(PO4)3 or its element substitution products,

[0139] (ii) (LaLi)TiO3-based perovskite solid electrolytes,

[0140] (iii)Li 14 ZnGe4O 16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their element substitution bodies,

[0141] (iv)Li7La3Zr2O 12 or its element substitution body, such as garnet-type solid electrolyte,

[0142] (v) Li3PO4 or its N-substituted form,

[0143] (vi) Glass or glass ceramics containing Li2SO4 or Li2CO3 added to a Li-BO compound such as LiBO2 or Li3BO3.

[0144] The electrolyte material contained in the positive electrode 101 may also be a polymer solid electrolyte.

[0145] Examples of polymer solid electrolytes include compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. Since polymer compounds having an ethylene oxide structure can contain a large amount of lithium salt, the ion conductivity can be further improved.

[0146] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. A mixture of two or more lithium salts selected from these may also be used.

[0147] The electrolyte material contained in the positive electrode 101 may also be a complex hydride solid electrolyte.

[0148] Examples of coordinated hydride solid electrolytes are LiBH4-LiI or LiBH4-P2S5.

[0149] The electrolyte material contained in the positive electrode 101 may also be a halide solid electrolyte. Examples of the halide solid electrolyte are the materials exemplified as the second solid electrolyte material.

[0150] The electrolyte material contained in the positive electrode 101 may be a halogen oxide solid electrolyte other than the first solid electrolyte material. Examples of the halogen oxide solid electrolyte are Li3OX or Li2HOX. Here, X is at least one element selected from Cl, Br and I.

[0151] The shape of the electrolyte material contained in the positive electrode 101 is not limited. Examples of the shape include needle-like, spherical, or ellipsoidal. For example, the electrolyte material may be in the form of particles.

[0152] When the electrolyte material contained in the positive electrode 101 is in the form of particles (e.g., spheres), the median particle size of the electrolyte material may be 100 μm or less or 10 μm or less. Thus, the positive electrode active material and the electrolyte material may be well dispersed in the positive electrode 101. As a result, the charge and discharge characteristics of the battery are improved.

[0153] The electrolyte material contained in the positive electrode 101 may also have a median particle size smaller than that of the positive electrode active material. As a result, the electrolyte material and the positive electrode active material can be dispersed more well in the positive electrode 101. As a result, the charge and discharge efficiency of the battery is improved.

[0154] To increase the energy density and output of the battery, in the positive electrode 101 , the ratio of the volume of the positive electrode active material to the total volume of the positive electrode active material and the volume of the electrolyte material may be 0.3 or more and 0.95 or less.

[0155] In order to increase the energy density and output of the battery, the positive electrode 101 may have a thickness of 10 μm or more and 500 μm or less.

[0156] The negative electrode 104 contains a negative electrode active material and an electrolyte material.

[0157] The negative electrode active material is a material that can intercalate and deintercalate metal ions (eg, lithium ions).

[0158] Examples of negative electrode active materials include metal materials, carbon materials, oxides, nitrides, tin compounds, or silicon compounds. The metal material may be either a single metal or an alloy. Examples of metal materials include lithium metal or lithium alloys. Examples of carbon materials include natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. In order to increase the capacity density, silicon (i.e., Si), tin (i.e., Sn), silicon compounds, or tin compounds may also be used as negative electrode active materials.

[0159] The negative electrode active material may also have a median particle size of 0.1 μm or more and 100 μm or less. When the negative electrode active material has a median particle size of 0.1 μm or more, the negative electrode active material and the electrolyte material can be well dispersed in the negative electrode 104. As a result, the charge and discharge characteristics of the battery are improved. When the negative electrode active material has a median particle size of 100 μm or less, the lithium diffusion rate in the negative electrode active material is increased. As a result, the battery can operate at a high output power.

[0160] The electrolyte material contained in the negative electrode 104 is, for example, a solid electrolyte.

[0161] The electrolyte material contained in the negative electrode 104 may be the same material as the second solid electrolyte material. In other words, the negative electrode 104 may contain the second solid electrolyte material.

[0162] The electrolyte material contained in the negative electrode 104 may be a material different from the second solid electrolyte material. Examples of such a material include the sulfide solid electrolyte, oxide solid electrolyte, polymer solid electrolyte, coordinated hydride solid electrolyte, or halide solid electrolyte exemplified as the electrolyte material contained in the positive electrode 101.

[0163] The shape of the electrolyte material contained in the negative electrode 104 is not limited. Examples of the shape include needle-like, spherical, or ellipsoidal. For example, the electrolyte material may be in the form of particles.

[0164] When the electrolyte material contained in the negative electrode 104 is in the form of particles (e.g., spheres), the median particle size of the electrolyte material may be 100 μm or less or 10 μm or less. Thus, the negative electrode active material and the electrolyte material can be well dispersed in the negative electrode 104. As a result, the charge and discharge characteristics of the battery are improved.

[0165] The electrolyte material included in the negative electrode 104 may have a smaller median particle size than the negative electrode active material. This allows the electrolyte material and the negative electrode active material to be well dispersed in the negative electrode 104 .

[0166] To increase the energy density and output of the battery, in the negative electrode 104 , the ratio of the volume of the negative electrode active material to the total volume of the negative electrode active material and the volume of the electrolyte material may be 0.30 to 0.95.

[0167] In order to increase the energy density and output of the battery, the negative electrode 104 may have a thickness of 10 μm or more and 500 μm or less.

[0168] In order to reduce the interface resistance, at least a portion of the surface of the positive electrode active material or at least a portion of the surface of the negative electrode active material may be covered with a covering material.

[0169] The coating material may use a material with low ion conductivity. Examples of the coating material are sulfide solid electrolytes, polymer solid electrolytes, coordinated hydride solid electrolytes, or halide solid electrolytes that have been exemplified as electrolyte materials contained in the positive electrode 101. In order to improve potential stability, an oxide solid electrolyte may also be used as the coating material. By using an oxide solid electrolyte as the coating material, the charge and discharge efficiency of the battery can be further improved.

[0170] Examples of oxide solid electrolytes used as coating materials are

[0171] (i) Li-Nb-O compounds such as LiNbO3,

[0172] (ii) Li-BO compounds such as LiBO2 or Li3BO3,

[0173] (iii) Li-Al-O compounds such as LiAlO2,

[0174] (iv) Li-Si-O compounds such as Li4SiO4,

[0175] (v) Li-SO compounds such as Li2SO4,

[0176] (vi)Li4Ti5O 12 Li-Ti-O compounds such as

[0177] (vii) Li-Zr-O compounds such as Li2ZrO3,

[0178] (viii) Li-Mo-O compounds such as Li2MoO3,

[0179] (ix) Li-VO compounds such as LiV2O5, or

[0180] (x) Li-WO compounds such as Li2WO4.

[0181] In order to increase the output power of the battery, at least one selected from the first electrolyte layer 102 and the second electrolyte layer 103 may also contain a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a coordinated hydride solid electrolyte exemplified as the electrolyte material contained in the positive electrode 101.

[0182] At least one selected from the positive electrode 101, the first electrolyte layer 102, the second electrolyte layer 103, and the negative electrode 104 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid in order to facilitate the transfer of lithium ions and improve the output characteristics of the battery.

[0183] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0184] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorinated solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorinated solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate, or dimethylene fluorocarbonate. One non-aqueous solvent selected therefrom may be used alone, or a mixture of two or more non-aqueous solvents selected therefrom may be used.

[0185] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone, or a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter or more and 2 mol / liter or less.

[0186] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte solution can be used. Examples of the polymer material include polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0187] Examples of cations contained in ionic liquids are

[0188] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,

[0189] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium, or piperidinium; or

[0190] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.

[0191] An example of an anion contained in an ionic liquid is PF6 - 、BF4 - 、SbF6 - 、AsF6 - 、SO3CF3 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - The ionic liquid may also contain a lithium salt.

[0192] At least one selected from the positive electrode 101 , the first electrolyte layer 102 , the second electrolyte layer 103 , and the negative electrode 104 may contain a binder in order to improve adhesion between particles.

[0193] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aromatic polyamide resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, polyhexafluoropropylene, styrene-butadiene rubber or carboxymethyl cellulose.

[0194] Copolymers can also be used as binders. Examples of such binders are copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more selected from the above materials can also be used as a binder.

[0195] At least one selected from the positive electrode 101 and the negative electrode 104 may contain a conductive auxiliary agent in order to improve electronic conductivity.

[0196] Examples of conductive additives are

[0197] (i) Graphite such as natural graphite or artificial graphite,

[0198] (ii) carbon black such as acetylene black or Ketjen black,

[0199] (iii) conductive fibers such as carbon fibers or metal fibers,

[0200] (iv) fluorinated carbon,

[0201] (v) Metal powders such as aluminum,

[0202] (vi) Conductive whiskers such as zinc oxide or potassium titanate,

[0203] (vii) conductive metal oxides such as titanium oxide,

[0204] (viii) Conductive polymer compounds such as polyaniline, polypyrrole, or polythiophene. In order to reduce costs, the above-mentioned (i) graphite or (ii) carbon black may also be used.

[0205] Examples of the shape of the battery of the first embodiment are a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.

[0206] <Method for producing the first solid electrolyte material>

[0207] The first solid electrolyte material is produced, for example, by the following method.

[0208] Raw material powders of oxides, hydroxides, halides, or oxyhalides are prepared to have a target composition. For example, when preparing LiNbOCl4, LiCl and NbOCl3 are prepared to have a molar ratio of 1:1.

[0209] The elements M and X in the chemical formula (1) are determined by selecting the type of raw material powder. The values ​​of α, β, γ and δ are determined by adjusting the raw material powder, the mixing ratio and the synthesis process.

[0210] The raw material powders are mixed to obtain a mixed powder. The mixed powders are reacted with each other in a mechanochemical manner (i.e., by a mechanochemical grinding treatment method) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant can also be sintered in a vacuum or in an inert gas atmosphere (e.g., an argon atmosphere or a nitrogen atmosphere). Alternatively, the mixture can be sintered in a vacuum or in an inert atmosphere to obtain a reactant. By these methods, the above-mentioned solid electrolyte material is obtained.

[0211] The composition of the solid electrolyte material can be determined by, for example, inductively coupled plasma emission spectrometry (ICP emission spectrometry), ion chromatography, inert gas fusion-infrared absorption, or EPMA (Electron Probe Micro Analyzer) analysis. However, since the measurement accuracy of the oxygen content is low, an error of about 10% may be included.

[0212] Example

[0213] The present invention will be described in detail with reference to Examples.

[0214] (Example 1)

[0215] [Production of the First Solid Electrolyte Material]

[0216] In a dry atmosphere with a dew point below -30°C (hereinafter referred to as "dry atmosphere"), LiCl and NbOCl3 are prepared as raw material powders in a manner to achieve a molar ratio of LiCl:NbOCl3=1:1. These mixtures are crushed in a mortar to obtain a mixed powder. The obtained mixed powder is treated at 600 rpm for 24 hours using a planetary ball mill (manufactured by Freech Co., Ltd.) to react mechanochemically. In this way, a powder of the first solid electrolyte material of Example 1 is obtained. The first solid electrolyte material of Example 1 has a composition represented by LiNbOCl4.

[0217] [Preparation of the Second Solid Electrolyte Material]

[0218] In a dry atmosphere, LiCl and YCl3 were prepared as raw material powders in a molar ratio of LiCl:YCl3=3:1. Except for this, the second solid electrolyte material of Example 1 was obtained in the same manner as the first solid electrolyte material of Example 1. The second solid electrolyte material of Example 1 had a composition represented by Li3YCl6.

[0219] [Measurement of reduction potential of solid electrolyte materials]

[0220] The reduction potential of the first solid electrolyte material of Example 1 was measured as follows.

[0221] In an insulating cylinder with an inner diameter of 9.5 mm, SUS foil, solid electrolyte material (100 mg) and Li foil are stacked in sequence to obtain a laminate. A pressure of 360 MPa is applied to the laminate. Next, a current collector formed of stainless steel is installed on the SUS foil and the Li foil, and a current collector lead is installed on the current collector. Finally, an insulating hoop is used to block the inside of the insulating cylinder from the outside air atmosphere and seal it. In this way, a battery (cell) for potential measurement is obtained.

[0222] The potential measurement cell was placed in a thermostatic chamber at 25° C. Cyclic voltammetry was used to perform a potential scan from −0.5 V to 6 V at a Li reference potential at a scan rate of 5 mV / s.

[0223] As a result, the first solid electrolyte material of Example 1 had a reduction potential of 2.9V.

[0224] The reduction potential of the second solid electrolyte material of Example 1 was measured in the same manner. As a result, the reduction potential of the second solid electrolyte material of Example 1 was 0.3V.

[0225] [Production of positive electrode materials]

[0226] In a dry atmosphere, the first solid electrolyte material of Example 1 and LiCoO2 (hereinafter referred to as "LCO") as a positive electrode active material were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. In this way, the positive electrode material of Example 1 was obtained.

[0227] [Manufacturing of Secondary Batteries]

[0228] In an insulating cylinder having an inner diameter of 9.5 mm, the positive electrode material (10 mg) of Example 1, the first solid electrolyte material (80 mg) of Example 1, and the second solid electrolyte material (80 mg) of Example 1 were sequentially stacked to obtain a laminate. A pressure of 360 MPa was applied to the laminate to form a positive electrode and a solid electrolyte layer.

[0229] Next, aluminum powder (20 mg) was stacked on the positive electrode side, and a pressure of 360 MPa was applied to the stacked body to form a current collector on the positive electrode side.

[0230] Next, a metal In foil (thickness 200 μm), a metal Li foil (thickness 300 μm), and a metal In foil (thickness 200 μm) were sequentially stacked on the solid electrolyte layer to obtain a stacked body. A pressure of 80 MPa was applied to the stacked body to form a negative electrode.

[0231] Current collectors made of stainless steel were placed on the positive electrode and the negative electrode, and current collecting leads were attached to the current collectors.

[0232] Finally, an insulating hoop was used to block the inside of the insulating tube from the outside air atmosphere and to seal it. In this way, the secondary battery of Example 1 was obtained.

[0233] (Example 2)

[0234] [Production of the First Solid Electrolyte Material]

[0235] In a dry atmosphere, LiCl and NbOCl3 were prepared as raw material powders in a molar ratio of LiCl:NbOCl3=0.9:1.0. Except for this, the first solid electrolyte material powder of Example 2 was obtained in the same manner as the first solid electrolyte material of Example 1. The first solid electrolyte material of Example 2 has Li 0.9 Nb 3.9 Represents the composition.

[0236] The reduction potential of the first solid electrolyte material of Example 2 was measured in the same manner as in Example 1. As a result, the reduction potential was 2.9V.

[0237] [Production of positive electrode materials]

[0238] In a dry atmosphere, the first solid electrolyte material of Example 2 and LCO were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. Thus, the positive electrode material of Example 2 was obtained.

[0239] [Manufacturing of Secondary Batteries]

[0240] A secondary battery of Example 2 was obtained in the same manner as the secondary battery of Example 1, except that the first solid electrolyte material and the positive electrode material of Example 2 were used instead of the first solid electrolyte material and the positive electrode material of Example 1.

[0241] (Example 3)

[0242] [Production of the First Solid Electrolyte Material]

[0243] In a dry atmosphere, Li2O2 and TaCl5 are prepared as raw material powders in a molar ratio of Li2O2:TaCl5=1:2. The mixture is crushed in a mortar to obtain a mixed powder. The obtained mixed powder is treated at 600 rpm for 24 hours using the above-mentioned planetary ball mill to react mechanochemically. Then, the mixed powder is calcined at 200°C for 6 hours. In this way, a powder of the first solid electrolyte material of Example 3 is obtained. The first solid electrolyte material of Example 3 has a composition of Li 1.2 TaO 1.3 Cl 3.6 Represents the composition.

[0244] The reduction potential of the first solid electrolyte material of Example 3 was measured in the same manner as in Example 1. As a result, the reduction potential was 2.3V.

[0245] [Production of positive electrode materials]

[0246] In a dry atmosphere, the first solid electrolyte material of Example 3 and LCO were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. In this way, the positive electrode material of Example 3 was obtained.

[0247] [Manufacturing of Secondary Batteries]

[0248] A secondary battery of Example 3 was obtained in the same manner as the secondary battery of Example 1, except that the first solid electrolyte material and the positive electrode material of Example 3 were used instead of the first solid electrolyte material and the positive electrode material of Example 1.

[0249] (Example 4)

[0250] [Preparation of the Second Solid Electrolyte Material]

[0251] In an argon atmosphere with a dew point below -60°C, prepare Li2S and P2S5 in a manner to achieve a molar ratio of Li2S:P2S5=75:25. The mixture is crushed in a mortar to obtain a mixed powder. Next, the mixed powder is treated at 510 rpm for 10 hours using the above-mentioned planetary ball mill to react mechanochemically to obtain a glassy solid electrolyte. The solid electrolyte is heat treated at 270°C for 2 hours in an inactive atmosphere. In this way, a powder of the second solid electrolyte material of Example 4, which is a glass-ceramic solid electrolyte, is obtained. The second solid electrolyte material of Example 4 has a composition represented by Li2S-P2S5.

[0252] The second solid electrolyte material of Example 4 is stable with respect to lithium.

[0253] [Manufacturing of Secondary Batteries]

[0254] The secondary battery of Example 4 is obtained in the same manner as the secondary battery of Example 1 except that the first solid electrolyte material of Example 3, the second solid electrolyte material of Example 4 and the positive electrode material of Example 3 are used instead of the first solid electrolyte material of Example 1, the second solid electrolyte material of Example 1 and the positive electrode material of Example 1.

[0255] (Comparative Example 1)

[0256] [Manufacturing of Secondary Batteries]

[0257] A secondary battery of Comparative Example 1 was obtained in the same manner as the secondary battery of Example 1 except that the first solid electrolyte material of Example 1 was used instead of the second solid electrolyte material of Example 1. That is, the secondary battery of Comparative Example 1 did not contain the second solid electrolyte material.

[0258] [Charge and discharge test]

[0259] The obtained secondary battery was placed in a constant temperature chamber at 25°C.

[0260] The secondary battery was charged at a current value of 60 μA, which is a 0.05 C rate (20 hour rate) with respect to the theoretical capacity of the battery, until the potential reached 4.2 V with respect to lithium.

[0261] Next, discharge was performed at a current value of 60 μA, which was also a 0.05 C rate.

[0262] The secondary batteries of Examples 1, 3, and 4 were discharged until the potential reached 2.5 V with respect to lithium. That is, the discharge end voltage was 2.5 V.

[0263] The secondary batteries of Example 2 and Comparative Example 1 were discharged until the potential reached 2.9 V with respect to lithium. That is, the discharge end voltage was 2.9 V.

[0264] The In—Li alloy used in the negative electrode of the secondary battery of the example and the comparative example has a potential of 0.6 V with respect to lithium.

[0265] As a result of the charge and discharge test, the initial discharge capacity and average discharge voltage of the batteries of Examples 1 to 4 and Comparative Example 1 were obtained. These values ​​are shown in Table 1.

[0266]

[0267] (Inspection)

[0268] As shown in Table 1, the batteries of Examples 1 to 4 have high discharge capacities.

[0269] Comparing Example 1 with Comparative Example 1 shows that when the first solid electrolyte material is in direct contact with the negative electrode, that is, when the battery does not have a second electrolyte layer, the discharge capacity of the battery is significantly reduced.

[0270] Comparison of Example 1 with Example 2 shows that the average discharge voltage of the battery is improved by setting the discharge end voltage of the battery to 2.9 V relative to lithium. This is believed to be because the reduction decomposition of the first solid electrolyte material is suppressed by setting the discharge end voltage to 2.9 V or more relative to lithium.

[0271] Comparison of Example 1 with Example 3 shows that when the first solid electrolyte material contains Nb as the element M, the discharge capacity of the battery is further improved.

[0272] Comparing Example 3 with Example 4, it is shown that the battery has a high discharge capacity regardless of whether the second solid electrolyte material is a sulfide solid electrolyte or a halide solid electrolyte.

[0273] Industrial Applicability

[0274] The battery of the present invention can be applied to, for example, an all-solid lithium ion secondary battery.

[0275] Explanation of symbols:

[0276] 1000 Batteries

[0277] 101 Positive electrode

[0278] 102 First electrolyte layer

[0279] 103 Second electrolyte layer

[0280] 104 Negative electrode

Claims

1. A battery comprising, in order, a positive electrode, a first electrolyte layer, a second electrolyte layer and a negative electrode, wherein: The first electrolyte layer contains a first solid electrolyte material, the second electrolyte layer contains a second solid electrolyte material which is a material different from the first solid electrolyte material, The first solid electrolyte material is represented by the following chemical formula (1): Li α M β O γ X δ (1) Here, α, β, γ, and δ are all values ​​greater than 0. M is at least one element selected from metal elements and semi-metal elements other than Li, X is at least one element selected from Cl, Br and I, and The second solid electrolyte material is a halide solid electrolyte other than an oxyhalide, or a sulfide solid electrolyte, The reduction potential of the second solid electrolyte material is lower than the reduction potential of the first solid electrolyte material.

2. The battery according to claim 1, wherein M contains at least one element selected from Nb and Ta.

3. The battery according to claim 1 or 2, wherein: In the chemical formula (1), 0.9≤α≤1.2、 β=1.0、 1.0≤γ≤1.3, and 3.6≤δ≤4.

0.

4. The battery according to claim 1 or 2, wherein The discharge end voltage is 2.9 V or more with respect to lithium.

5. The battery according to claim 1 or 2, wherein The second solid electrolyte material is represented by the following chemical formula (2): Li p M' q X' r (2) Here, p, q, and r are all values ​​greater than 0. M' is at least one element selected from metal elements and semi-metal elements other than Li, X' is at least one element selected from the group consisting of Cl, Br and I.

6. The battery according to claim 5, wherein M' comprises yttrium.

7. The battery according to claim 5, wherein M' is yttrium, p=3, q=1 and r=6 are satisfied.

8. The battery according to claim 1, wherein The sulfide solid electrolyte includes lithium sulfide and phosphorus sulfide.

9. The battery according to claim 1, wherein The sulfide solid electrolyte is Li2S-P2S5.

10. The battery according to claim 1 or 2, wherein The positive electrode contains the first solid electrolyte material.

Citation Information

Patent Citations

  • All-solid lithium secondary battery

    JP2006244734A

  • Secondary battery

    CN104054210A

  • Battery system, method for manufacturing battery system, and battery control apparatus

    CN104364956A